A novel elastomer-based magnetoresistive accelerometer - Phan, K.L.; Mauritz, A.; Homburg, F.G.A. (Sensors and actuators. A. Physical., 2008)
In this paper, we present a novel type of biaxial accelerometer based on a polydimethylsiloxane (PDMS) structure as the mass–spring system and using magnetoresistive (MR) sensors as the detection method. The proof mass of the sensor is a mushroom-shaped polymer magnet made of PDMS filled with permanent magnet powder, whose minute movement under lateral acceleration is precisely sensed by a set of MR sensors. The device aims at consumer electronics applications of low g range and low frequency, such as inclination measurements and motion sensing. An experimental device has been successfully fabricated which showed a linear transfer curve without significant hysteresis. A sensitivity of 0.32mV/(Vg) was obtained.